Visionary Leadership of School Administrators under Kanchanaburi Primary Educational Service Area Office 1 - มะหามิตร, แววดาว; แก้วมงคล, ทรงยศ; พรธิวา , พรธิวา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were 1) to study the visionary leadership of school administrators; 2) to compare their visionary leadership based on personal factors, including gender, age, educational level, and work experience; and 3) to identify guidelines for developing the visionary leadership of school administrators under Kanchanaburi Primary Educational Service Area Office 1. The sample consisted of 310 school administrators and teachers, determined using the Krejcie & Morgan table and selected through stratified random sampling based on school size, followed by simple random sampling. Research instruments included a 5-point Likert scale questionnaire with an Index of Item-Objective Congruence (IOC) between 0.60 and 1.00 and a reliability of .891, and semi-structured interviews. The qualitative study involved 5 key informants, selected through purposive sampling, who held a master's degree in educational administration. Quantitative data were analyzed using frequency, percentage, mean, and standard deviation. Hypotheses were tested using t-test and F-test (One-way ANOVA). Qualitative data were analyzed using content analysis.              The research findings were as follows 1) The visionary leadership of school administrators was overall at a high level. When considering each aspect, all four areas were also at a high level, ranked by mean as follows: Vision. 2) Comparisons of visionary leadership based on gender, age, educational level, and work experience showed no significant differences at the .05 level in either the overall or individual aspects, which did not support the research hypothesis. This might be due to the fact that administrators have been cultivated with competencies through consistent professional development and position standards provided by the parent organization. Additionally, equal access to administrative innovations in the digital age has led to vision expressions that focus more on institutional goals than individual factors. 3. Development guidelines for visionary leadership comprised four key areas. 1) Vision Creation, 2) Vision Dissemination, 3) Vision Implementation, and 4) Being a Good Role Model. All four areas must be implemented systematically and in line with the current educational management context to lead educational institutions toward sustainable success.